2011
DOI: 10.5858/arpa.2011-0157-ra
|View full text |Cite
|
Sign up to set email alerts
|

Assuring Quality in Point-of-Care Testing: Evolution of Technologies, Informatics, and Program Management

Abstract: Objectives.-To present the evolving role of technology improvement, informatics, and program management as the key developments to ensure the quality of POCT.Data Sources.-This presentation is based on a review of the literature and on our experiences with POCT at the Massachusetts General Hospital (Boston).Conclusions.-Federal and state regulations, along with accreditation standards developed by the College of American Pathologists and The Joint Commission, have established guidelines for the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 9 publications
2
47
0
1
Order By: Relevance
“…Investigations should address the adequacy of POCT oversight; provide education regarding the importance of QC for both regulatory compliance and patient care; establish institutional policy and training of both POCT personnel and supervisors; ensure competency in POCT instrumentation, software, and design regarding QC; and monitor QC performance and compliance, as well as any other variables that may affect the POCT program at an institution. Some authors 2,6 have suggested solutions such as increased oversight by a dedicated POCT supervisor, improved or reeducation of POCT personnel, and enhanced QC design features, such as instrument locks in the event of a QC failure.…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations should address the adequacy of POCT oversight; provide education regarding the importance of QC for both regulatory compliance and patient care; establish institutional policy and training of both POCT personnel and supervisors; ensure competency in POCT instrumentation, software, and design regarding QC; and monitor QC performance and compliance, as well as any other variables that may affect the POCT program at an institution. Some authors 2,6 have suggested solutions such as increased oversight by a dedicated POCT supervisor, improved or reeducation of POCT personnel, and enhanced QC design features, such as instrument locks in the event of a QC failure.…”
Section: Commentsmentioning
confidence: 99%
“…However, achieving compliance with regulatory guidelines and ensuring the quality of POCT has proved challenging in many institutions. 6 In the authors' experience, performance of traditional QC is a misunderstood and undervalued concept for many nonlaboratory personnel because they are largely unfamiliar …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Managed by the central laboratory this executive group is committed to fulfilling the regulations for quality management and improving the whole process. 77 The POCT committee is the right place for actively fulfilling the spirit of partnership and should meet at least once a year. It is important that clinical POCT users have participation in decision making.…”
Section: Organization Related Issues Hpoct Coordinationmentioning
confidence: 99%
“…The calibration activities for the devices and confirmation of the measurable range of the instrument must also be performed for each device before clinical use. 10 Quality control is another key challenge. Organizations are required to perform and maintain documentation for the calibration activities based on the manufacturer's recommendations for the product.…”
mentioning
confidence: 99%